Morphometric and ultrastructural analysis of different pituitary cell populations in undernourished monkeys - Console de Avegliano, Gloria Miriam (2001)
Undernutrition elicited by a low-protein diet determines a marked reduction of hypophyseal activity and affects the function of the respective target organs. The objective of the present investigation was to study the ultrastructural and quantitative immunohistochemical changes of the different pituitary cell populations in undernourished monkeys that had been previously shown to have significant changes in craniofacial growth. Twenty Saimiri sciureus boliviensis monkeys of both sexes were used. The animals were born in captivity and were separated into two groups at one year of age, i.e., control and undernourished animals. The monkeys were fed ad libitum a 20% (control group) and a 10% (experimental group) protein diet for two years. Pituitaries were processed for light and electron microscopy. The former was immunolubeled with anti-GH, -PRL, -LH, -FSH, -ACTH, and -TSH sera. Volume density and cell density were measured using an image analyzer. Quantitative immunohistochemistry revealed a decrease in these parameters with regard to somatotrophs, lactotrophs, gonadotrophs and thyrotrophs from undernourished animals compared to control ones. In these populations, the ultrastructural study showed changes suggesting compensatory hyperfunction. On the contrary, no significant changes were found in the morphometric parameters or the ultrastructure of the corticotroph population. We conclude that in undernourished monkeys the somatotroph, lactotroph, gonadotroph, and thyrotroph cell populations showed quantitative immunohistochemical changes that can be correlated with ultrastructural findings.